A Walk Through Prague : Actions Performances Happenings : 1949-1989 - Morganova, Pavlina (Prague : Academy of Fine Arts, 2017)
Aktual Art ; Boudnik, Vladimir ; Brikcius, Eugen ; Büchler, Pavel ; Hladik, Lumir ; K.Q.N. ; Kafka, Ivan ; Kmentova, Eva ; Knizak, Milan ; Kovanda, Jiri ; Kozelka, Milan ; Order of Crusaders of Pure Humor without Banter ; Miler, Karel ; Mlcoch, Jan ; Petrivy, Tomas ; Ruller, Tomas ; Saglova, Zorka ; Sozanksy, Jiri ; Stembera, Petr ; Svecova, Sona ; Wittmann, Robert
A Walk Through Prague provides an insider´s guide to the locations of over 150 performances, happenings and other such actions that took place in both the city´s tourist-frequented places and its half forgotten nooks in 1949-1989. This book will usher anyone wanting to learn more about Czech post-war art through a unique time and space, offering an alternative view of Prague and its history. (text publisher)
boek
Keywords: Tsjechië